The Impact of Family Parenting Patterns on Students' Self-Confidence in Socializing in the Community in Rambung Dalam, South Binjai - Ananda Indri Anisya; Juliani; Ihsan Maulana; Mhd Abdi Fadillah Ritonga; Mhd Raihan Nasution (Journal of Contemporary Gender and Child Studies, 2025)
Parenting style plays a crucial role in shaping a child's personality and selfconfidence from an early age. Self-confidence is a key psychological aspect needed for successful social interaction, especially for university students who are increasingly exposed to broader social environments. Students in Rambung Dalam, Binjai Selatan, come from diverse family backgrounds, which results in varied parenting styles and levels of self-confidence. This study aims to analyze how parenting styles influence students' self-confidence in their social interactions within the community. This research employs a qualitative approach using a descriptive method. Data collection techniques include in-depth interviews, direct observation, and documentation involving students residing in Rambung Dalam who have experienced different forms of parental upbringing. The participants were selected purposively based on specific criteria, such as living with their parents or having a clear history of parental involvement. The findings reveal that students raised in a democratic parenting environment tend to have higher self-confidence. They communicate effectively, participate actively in social activities, and are not afraid to express their opinions. In contrast, students who were raised with an authoritarian parenting style often exhibit passive behavior, self-doubt, and social withdrawal. Meanwhile, those who experienced permissive parenting tend to have unstable self-confidence, especially when faced with social pressures or responsibilities. The study concludes that parenting style significantly affects the development of students’ self-confidence. A supportive, communicative, and balanced parenting style is essential in fostering confident individuals who can engage in healthy social interactions within the community. These findings highlight the importance of proper parenting in shaping young adults who are self-assured, socially adaptable, and capable of contributing positively to society.